Safety Management Model Based on the Standardization of Processes and 5S to Reduce the Rate of Intoxication in SMEs in the Chemical Sector - Lamas Salazar, Gonzalo Ricardo (2022)
The chemical industry has showed steady growth in recent years and, as a result, the rate of intoxication has increased from the use of dangerous substances by employees of manufacturing companies. Therefore, small & medium enterprises (SMEs) in this industry must be committed to ensuring and guaranteeing safe and ergonomic workstations for employees that are mostly exposed to these risks to prevent incidents and reduce rates to a minimum when handling chemicals to produce paints and varnishes, and, at the same time, improve employee motivation and productivity. For this reason, this paper proposes the implementation of a safety management model based on process standardization and 5S for the purpose of promoting best practices in occupational safety and health, thereby reducing the number of intoxications within company grounds through employee collaboration in the improvement and optimization of working conditions, time management and resource use efficiency. This model is expected to achieve the reduction of intoxications by 40% after its implementation in a period of 10 months, furthermore, a series of simulations will be carried out to validate the results.